+0  
 
+1
42
2
avatar+238 

Solve. Remeber to chack for extraneous solutions.

 

Thank you so much!!!!!!!!!!!!!!!!!!!!!!!!!

KennedyPape  Nov 3, 2018
 #1
avatar+91213 
+2

-1  =  sqrt ( 3x - 2)  - sqrt (4x + 1)

sqrt (  4x+ 1) - 1  = sqrt (3x - 2)     square both sides

4x+ 1 -  2sqrt(4x + 1)  + 1  =  3x - 2   rearrange as

x + 4  =  2sqrt (4x + 1)    square both sides once more

x^2 + 8x + 16  = 4(4x + 1)

x^2 + 8x + 16 = 16x + 4

x^2 - 8x + 12  = 0    factor

(x - 6) ( x - 2)  = 0

 

Set each factor to 0 and solve for x and we have that  x = 6  or x = 2

 

Both solutions check out in the original equation !!!

 

 

 

cool cool cool

CPhill  Nov 3, 2018
 #2
avatar+238 
+1

Hello cphill,

 

Could you please answer my other question i posted titled "Please help me. This is the last question I don't understand. (11/2/19)" The person who answered it didn't really explain and im having trouble understanding it. 

 

-k

KennedyPape  Nov 3, 2018

33 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.